2013
DOI: 10.1016/j.ultsonch.2013.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical effect on size reduction of CaCO3 nanoparticles derived from waste eggshells

Abstract: A novel combination of mechanochemical and sonochemical techniques was developed to produce high-surface-area, bio-based calcium carbonate (CaCO3) nanoparticles from eggshells. Size reduction of eggshell achieved via mechanochemical and followed by sonochemical method. First, eggshells were cleaned and ground, then ball milled in wet condition using polypropylene glycol for ten hours to produce fine particles. The ball milled eggshell particles were then irradiated with a high intensity ultrasonic horn (Ti-hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 47 publications
3
59
0
Order By: Relevance
“…Char is also responsible for the impermeability of volatile components which accelerates combustion . ENP is porous in nature, hence, it can permit the infiltrations of volatile components to accelerate thermal decomposition. However, delays in 5% decomposition is due blockage of the pores by early stage char formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Char is also responsible for the impermeability of volatile components which accelerates combustion . ENP is porous in nature, hence, it can permit the infiltrations of volatile components to accelerate thermal decomposition. However, delays in 5% decomposition is due blockage of the pores by early stage char formation.…”
Section: Resultsmentioning
confidence: 99%
“…However, another report showed improvement in thermal stability with bioplast GS 2189 . The increase in residue is because of the presence of proportionate amount of CaO from the transformation of ENP in the composites at higher temperature and char from the matrix which contributed to retard thermal degradation …”
Section: Resultsmentioning
confidence: 99%
“…Beyond plant sources, a combination of ball-milling and ultrasound can reduce other organic material sources such as waste eggshells into calcium carbonate nanoparticles (Hassan et al, 2013).…”
Section: R Bell and Othersmentioning
confidence: 99%
“…78 of different sizes and shapes with different surface areas in various solvents. 79 These nanotechnology processes are respectively analogous to homeopathic manual trituration in dry lactose or succussions in liquid solutions. 79,81,86 One nanotechnology group found that combining milling with ultrasound agitation of the solutions was most effective for creating and dispersing the resultant NPs compared with either method by itself.…”
Section: Figure 2 Top Down and Bottom Up Manufacturing Strategies Formentioning
confidence: 99%